2022
DOI: 10.1021/acs.cgd.2c01009
|View full text |Cite
|
Sign up to set email alerts
|

Steering Interzeolite Conversion with Alkali Metal Cations: Lithium Maximizes Al Proximity in SSZ-13 Zeolite Genesis

Abstract: Zeolites have long been regarded as difficult to modify during synthesis, as their synthesis is governed by kinetic processes. Recent breakthroughs have made it possible to exert a certain degree of control over zeolite properties with more performant materials as a result. Here, we investigate the effects alkali cations have on high-silica FAU-to-CHA interzeolite conversion (IZC) and on the resulting aluminum distributions. In this way, by using Li-cations in conjunction with an organic structure directing ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…The Dusselier group recently reported an intriguing study of conversion to SSZ-13 and differential crystallization times with the greatest enhancement coming from lithium. 28 In our current study we have shown that there is a much faster reaction for the use of CBV-720 as Si and Al sources in the reaction than the intermediate system of NaY and sodium silicate, or sodium silicate and a soluble Al source at the start of the reaction mixing like aluminum sulfate or a hydrated alumina trihydroxide. We showed that even the degraded CBV-720 converts quickly.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…The Dusselier group recently reported an intriguing study of conversion to SSZ-13 and differential crystallization times with the greatest enhancement coming from lithium. 28 In our current study we have shown that there is a much faster reaction for the use of CBV-720 as Si and Al sources in the reaction than the intermediate system of NaY and sodium silicate, or sodium silicate and a soluble Al source at the start of the reaction mixing like aluminum sulfate or a hydrated alumina trihydroxide. We showed that even the degraded CBV-720 converts quickly.…”
Section: Discussionmentioning
confidence: 58%
“…It is also important to note that, in the OSDA-free syntheses, the solvated alkali metal cations become important. The Dusselier group recently reported an intriguing study of conversion to SSZ-13 and differential crystallization times with the greatest enhancement coming from lithium …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, previous modeling and indirect measurements inferred from Co 2+ titration have indicated that the rate of methanol dehydration over H + -chabazite may be faster over catalysts in which framework Al heteroatoms are near one another, compared to when they are isolated. Here, two H + -chabazite catalysts were tested for the rates at which methanol was converted to dimethyl ether under identical conditions (Figure ). The two zeolites were both synthesized using trimethyladamantylammonium hydroxide as the organic structure-directing agent, although H + -CHA-1 was synthesized via interzeolite conversion using FAU zeolite as a precursor, while H + -CHA-2 was synthesized by conventional methods using molecular precursors. The resulting products had very similar bulk compositions (Si/Al ∼ 10) and were indistinguishable by conventional scattering or NMR characterization techniques (Figures S1–S4) or their 2D 1 H– 1 H NMR spectra (Figure S5). Notably, standard Co 2+ exchange analyses resulted in low Co 2+ /Al ratios of <0.02 for both catalysts (Table S1).…”
mentioning
confidence: 99%